2010
DOI: 10.1159/000317635
|View full text |Cite
|
Sign up to set email alerts
|

M1 Protein-Dependent Intracellular Trafficking Promotes Persistence and Replication of <i>Streptococcus pyogenes</i> in Macrophages

Abstract: Streptococcus pyogenes is an important human pathogen that causes a variety of diseases including life-threatening invasive diseases, such as toxic shock and deep tissue infections. Although S. pyogenes are classically considered extracellular pathogens, a clinical significance of an intracellular source has been emphasized. In patients with deep tissue infections, an intracellular reservoir of S. pyogenes within macrophages was shown to contribute to prolonged bacterial persistence. Here we demonstrate that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 77 publications
10
75
0
5
Order By: Relevance
“…Isolation of monocytes was performed essentially as previously described (31,32). In brief, CD14 ϩ monocytes were isolated from buffy coats by negative selection using RosetteSep human monocyte enrichment cocktail (0.5 ml/10 ml blood; StemCell Technologies, Vancouver, Canada) and separated on Ficoll-Paque Plus.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of monocytes was performed essentially as previously described (31,32). In brief, CD14 ϩ monocytes were isolated from buffy coats by negative selection using RosetteSep human monocyte enrichment cocktail (0.5 ml/10 ml blood; StemCell Technologies, Vancouver, Canada) and separated on Ficoll-Paque Plus.…”
Section: Methodsmentioning
confidence: 99%
“…Co gorsze, bakterie mają-ce na swojej powierzchni ekspresję białka M1 wykazują zdolność do unikania połączeń z lizozymami wewnątrz makrofagów. Powoduje to stan, w którym makrofagi stanowią nie tylko bezpieczny rezerwuar pozwalający przetrwać paciorkowcom, ale dochodzi w nich wręcz do replikacji bakterii [15]. Jest to szczególnie niebezpieczne zjawisko będące podstawą patogenności i zdolności wywołania wstrząsu septycznego.…”
Section: Dyskusjaunclassified
“…Although S. pyogenes has been considered as an extracellular pathogen, various reports have shown that it invades different cell types in vitro including epithelial cells [4,5,6], neutrophils [7,8] and macrophages [9,10]. Internalization of S. pyogenes into eukaryotic cells is considered to be one successful mechanism for evading host immune responses and penicillin treatment, and it may thus promote transmission and dissemination from the primary side of infection.…”
Section: Introductionmentioning
confidence: 99%